Radiopacity evaluation of root-end filling materials by digitization of images - Mario Tanomaru-Filho; Guilherme Ferreira da Silva; Marco Antonio Húngaro Duarte; Marcelo Gonçalves; Juliane Maria Guerreiro Tanomaru (University of São Paulo, 2008)
The purpose of this study was to evaluate the radiopacity of 5 root-end filling materials (white MTA-Angelus, grey MTA-Angelus, IRM, Super EBA and Sealer 26). Five specimens (10 mm diameter X 1 mm thickness) were made from each material and radiographed next to an aluminum stepwedge varying in thickness from 2 to 16 mm. Radiographs were digitized and the radiopacity of the materials was compared to that of the aluminum stepwedge using VIXWIN 2000 software in millimeters of aluminum (mm Al). Data were analyzed statistically by ANOVA and Tukey's test at 5% significance level. Radiopacity values varied from 3 mm Al to 5.9 mm Al. Sealer 26 and IRM presented the highest radiopacity values (p<0.05), while white/grey MTA and Super EBA presented the lowest radiopacity values (p<0.05). The tested root-end filling materials presented different radiopacities, white/grey MTA and Super EBA being the least radiopaque materials.